Intestinal microbes influence the survival, reproduction and protein profile of Trichinella spiralis in vitro. Issue 1 (January 2016) - Jiang, Hai-yan; Zhao, Na; Zhang, Qiao-ling; Gao, Jiang-ming; Liu, Li-li; Wu, Teng-Fei; Wang, Ying; Huang, Qing-hua; Gou, Qiang; Chen, Wei; Gong, Peng-tao; Li, Jian-hua; et al.
Graphical abstract: Highlights: Some intestinal microbes have similar effects in the humans and nematodes. Metabolic acceleration is one of the protective responses of Trichinella spiralis to Escherichia coli O157:H7 (EHEC). PMK-1 and insulin signalling pathways were involved in defence against EHEC and Salmonella enterica . Abstract: The interactions between intestinal microbes and parasitic worms play an essential role in the development of the host immune system. However, the effects of gut microbes on Trichinella spiralis are unknown. The aim of this work was to explore microbe-induced alterations in the survival and reproduction of T. spiralis in vitro. To further identify the proteins and genes involved in the response of nematodes to microbes, quantitative proteomic analysis of T. spiralis was conducted by iTRAQ-coupled LCMS/MS technology and quantitative real-time-PCR was used to measure changes in mRNA expression. The results showed Lactobacillus acidophilus, and especially Lactobacillus bulgaricus, significantly enhanced the survival and reproductive rates of nematodes. Salmonella enterica, and especially Escherichia coli O157:H7 (EHEC), had opposite effects. Genetic responses were activated mainly by EHEC. A total of 514 proteins were identified and quantified, and carbohydrate metabolism-related proteins existed in a higher proportion. These findings indicated that some gut bacteria are friendly or harmful to humans and in addition they may have similar beneficial or detrimental effects on parasites. This may be due to the regulation of expression of specific genes and proteins. Our studies provide a basis for developing therapies against parasitic infections from knowledge generated by studying the gut microbes of mammals.